Field-to-Wire Coupling Model for Wire Bundles with Strongly Non-uniform Path - Xinwei Song; Donglin Su; Junjun Wang; Bing Li (Applied Computational Electromagnetics Society Journal (ACES), 2019)
This paper presents a field-to-wire coupling model for wire bundles with strongly non-uniform path. Previous studies on multi-conductor transmission lines (MTL) are mainly confined to uniform or weakly nonuniform path, which is sometimes not the case in practice. In this paper, the external and internal characteristics of the wire bundle are decomposed by a mode transformation method, of which the advantage is the transformation matrices do not vary with the nonuniform path. The external characteristics correspond to common-mode (CM) components, modeled as an equivalent single wire running in the same path with the bundle above the reference ground. The internal characteristics correspond to differential-mode (DM) components, modeled as a uniform MTL system composed of the original wires in the bundle. In this way, the effects of the non-uniform path and the external field only exist in the CM model. Mode conversion caused by the dielectric coating and terminals is modeled with equivalent circuits. The proposed model is validated with a bundle of curved wires above a PCB board.